THE EFFECT OF TIME MANAGEMENT, SELF-EFFICACY, AND STUDY MOTIVATION ON ACADEMIC PROCRASTINATION IN THE COMPLETION OF STUDY PROCESS STUDENTS OF THE ECONOMICS EDUCATION STUDY PROGRAM, FACULTY OF ECONOMICS, STATE UNIVERSITY OF JAKARTA - Pramono, Irma Yulia; Nurjanah, Siti; Nikensari, Sri Indah (International Journal of Multidisciplinary Research and Literature, 2024)
This study aims to determine the extent to which time management, self-efficacy, and learning motivation affect academic procrastination. The methodology in this study is based on quantitative research. The sampling technique used simple random sampling by selecting batches 2017, 2018, and 2019 as samples and populations. The population in this study was 152, and the sample was 110 students who were working on their final project. The data collection technique used a questionnaire in the form of a closed statement via google form link and data analysis. In the results of this study, 77.3% of the variables of time management, self-efficacy, and learning motivation affect academic procrastination. While the remaining 27.7% is not tested in this study. The results show: time management positively affects learning motivation, self-efficacy postively affects learning motivation, time management negatively affects academic procrastination, self-efficacy negatively affects academic procrastination, learning motivation negatively affects academic procrastination, time management through learning motivation affects academic procrastination, self-efficacy through learning motivation affects academic procrastination